PRIDE IN KENNY CHESNEY’S “AMERICAN KIDS” - Mahartini, Gita (LANTERN (Journal on English Language, Culture and Literature), 2016)
This extended essay discusses the representation of the behavior of American kids as seen through their life styles reflected on Kenny Chesney “American Kids”. The behavior is well portrait through the lyric, but the lyric itself has not been reviewed sufficiently. The purposes of this extended essay are to describe the behavior literally and figuratively, and also to construct the meaning related to the description of the lyric. The writer analyzes the study using library research and she adopts the psychology of behavior by B.F Skinner as her approach method. The result of the analysis shows the description of American kids behavior literally and figuratively as pride in American kids reflected on “American Kids”. Therefore, it can be concluded that the song lyric of American Kids reflects the representation of American kids behavior.